AB1355 Observed dosing and refill compliance in bio-naÏve and bio-experienced psoriatic arthritis patients treated with golimumab. (23rd January 2014) - Ellis, L.; Haas, S.; Bolge, S.; Tandon, N.
Abstract : Background: Golimumab is a once-monthly, subcutaneously-administered, anti-TNF agent indicated for treatment of active psoriatic arthritis (PsA). Real-world dosing and refill compliance patterns of golimumab use in PsA patients have not been reported previously. Objectives: This study reports golimumab (GLM) dosing and refill compliance observed in psoriatic arthritis (PsA) patients. Methods: This retrospective database analysis assessed GLM use in adult PsA patients with ≥2 GLM prescriptions between 4/24/2009 and 12/31/2010; ≥1 PsA diagnosis during the study period; continuous activity in the Source® LX database (≥6 months before; ≥6 months after the index GLM prescription; and a 28-31 day GLM supply. Refill compliance was defined as refills occurring ± 1 week of the expected 28-31 day (d) interval. The percent of compliant GLM refill intervals and the percent of patients demonstrating refill compliance at the 6th GLM dose were assessed in the overall population and in bio-naïve/bio-experienced subgroups. Descriptive statistics were used to characterize the study population (mean ± SD, median, n and %). Results: A total of 262 PsA patients and 1, 489 GLM refill intervals were observed. The sample was 59% female; mean age of 50 years with 72% bio-experienced. A 50 mg GLM dose was found in 97% of all fills. The mean±SD refill interval for the overall population was 35.6±19.8 d with a median of 31 d. Bio-experienced patients had slightly more frequent refill intervals (34.9±18.4 d) as compared to bio-naïve patients (37.4±23.2 d), but the median was 31 d in both subgroups. Refill compliance was observed in 80% of all intervals for the overall population. Refill compliance at the 6th GLM dose was achieved by 84% of patients overall; (87% of bio-naïve and 82% of bio-experienced patients). Conclusions: In this retrospective analysis of a large national administrative claims database, 97% of GLM doses were 50 mg with approximately once monthly refill intervals. Overall refill compliance was observed in approximately 80% of all GLM refills and in greater than 80% of PsA patients at the sixth GLM dose. Median refill interval and refill compliance appeared similar in bio-experienced and bio-naïve subgroups. Further study of these trends using additional data sources are desired to substantiate these preliminary findings. Disclosure of Interest: L. Ellis Employee of: Janssen Scientific Affairs, LLC, S. Haas Consultant for: Janssen Scientific Affairs, LLC, S. Bolge Employee of: Janssen Scientific Affairs, LLC, N. Tandon Employee of: Janssen Scientific Affairs, LLC